2020
DOI: 10.2185/jrm.2020-002
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional case conferences to bridge perception gaps regarding ethical dilemmas in home-based end-of-life care: a qualitative study

Abstract: Objective: The aim of this study was to examine the effectiveness and efficiency of interprofessional case conferences on home-based end-of-life care to bridge perceptions gaps regarding ethical dilemmas among different healthcare professionals and analyze essential issues extracted the interprofessional discussions. Patients and Methods: The participants could spend only a limited amount of time after their working hours. Therefore, we shortened and simplified each of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…In-depth interview skills are essential for doctors, especially psychiatrists and palliative care clinicians 34,35) . Social workers receive intensive training in in-depth interviewing techniques as part of their education, and recognize person-centered interviewing with their clients as their responsibility within the interdisciplinary care team [36][37][38] . However, physicians tend to prefer dealing with informed consent, which is at the heart of decision making, and are generally ill-prepared to discuss broader aspects such as patients' personal values and preferences 39) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In-depth interview skills are essential for doctors, especially psychiatrists and palliative care clinicians 34,35) . Social workers receive intensive training in in-depth interviewing techniques as part of their education, and recognize person-centered interviewing with their clients as their responsibility within the interdisciplinary care team [36][37][38] . However, physicians tend to prefer dealing with informed consent, which is at the heart of decision making, and are generally ill-prepared to discuss broader aspects such as patients' personal values and preferences 39) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature suggested that the learning and practical experience of interprofessional teams working on common goals to improve patient outcomes increased understanding, shared values, and respect for the roles of other healthcare professionals 46,47) . For example, interprofessional case conferences with end-of-life case scenarios involving sensitive moral and ethical issues improved healthcare professionals' communication and conflict resolution skills 38) and ethically difficult cases that need to be resolved quickly, there are usually multiple factors to consider including patients' values and preferences, and relatives' concerns and values. In these situations, interprofessional case conference participants could resort to a widely used systematic approach such as the four topics approach to clinical ethical case analysis described by Jonsen et al 48) to collect necessary data and ensure the success of the conflict resolution strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevenção (previsão de possíveis complicações e/ou sintomas afim de evitar sofrimentos desnecessários); 5. Não abandono (a permanência junto ao paciente, garantindo a comunicação empática para auxiliá-lo em suas decisões) (12,13).…”
Section: Fonte: Elaborado Pelos Autores 2024unclassified
“…While ACP provides healthcare professionals with valuable tools to meet patients' needs in a person-centered manner, several potential ethical challenges are inherent in the process [4,5]. Ethical dilemmas and conflicts (i.e., withholding aggressive management, withdrawing life-sustaining treatment, ascertaining patient autonomy) can arise in endof-life care when a difficult problem cannot be solved in a way that will satisfy everyone involved [5]. Thus, ethical reasoning is a significant component of ACP that affects the actions of patients, their families, and healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%